Relationship between QTc interval prolongation and mortality of acute ischaemic stroke patients during treatment and three months after treatment at Adam Malik Hospital - Lubis, Al-Ma’ Arij Akbar; Andra, Cut Aryfa; Ketaren, Andre Pasha (CoinReads Media Prima, 2024)
Introduction: QTc interval prolongation is associated with an increased risk of mortality and incident cardiocerebrovascular disease in high-risk individuals and the general population. In addition, QTc interval prolongation in patients with acute stroke is associated with a significantly greater risk of death within 3 months. Based on the description in the background above, this study aims to determine how the relationship of QTc interval prolongation to mortality in acute ischaemic stroke patients during treatment and three months post-treatment at H. Adam Malik Hospital Medan. Method: This study was an analytical study with a case control research design to determine the relationship of QTc interval prolongation to mortality in acute ischaemic stroke patients during treatment and three months post-treatment at Adam Malik Hospital Medan. The research time was carried out in March 2023 by taking a sample of cases from January 2021 to December 2022. The association of QTc interval prolongation with mortality of acute ischaemic stroke patients during treatment and three months post-treatment was analysed by Chi-square test. The statistical significance threshold used was p < 0.05. Results: In patients who died, the mean QTc interval was 490 ms (453.0 - 547.0 ms). Comorbidities in this study included 27 (32.9%) patients with Type 2 DM, 42 (51.2%) patients with hypertension, 7 (16.6%) patients with chronic kidney disease, 13 (15.8%) patients with atrial fibrillation, 1 (1.21%) with pneumonia, and 1 (1.21%) with upper feeding tract bleeding (PSMBA). Conclusion: QTc interval prolongation is associated with mortality in acute ischaemic stroke patients during treatment and three months post-treatment at H. Adam Malik Hospital Medan